DESINING A DIGITAL PLATFORM FOR PHYSICAL SPORTS PEDAGOGICAL ACTIVITIES FOR SECONDARY STUDENTS - فوايزية بلال; جبلي مريم (My University, 2024)
Abstract: Our study aims to design a digital platform for educational physical and sports activities for secondary school students. The researchers relied on the descriptive survey method. The sample of the study was teachers of physical education and sports for the secondary stage “District 01” of the state of Souk Ahras, estimated at 40 teachers, relying on a questionnaire form as a tool. For research, the Ka test was used to analyze the data, and the researchers concluded: - The videos on this platform facilitate the educational process by providing high-quality educational content from anywhere and at any time that suits the needs and level of the students, which enhances their understanding and understanding. - Enhancing interaction between the professor and students through synchronous and asynchronous chat and through advanced assessment tools on a continuous and accurate basis, which helps in identifying strengths and weaknesses. - It enables teachers to design and present educational content in innovative and attractive ways that increase students’ motivation and desire to participate and practice. The researchers recommended: 1. Videos should be of high quality in terms of image and sound, and provide clear and detailed explanations of sports techniques. 2. Platforms must include additional educational resources such as articles, studies, and research that support sports content. : الملخص تهدف دراستنا إلى تصميم أرضية رقمية للأنشطة البدنية والرياضية التربوية لتلاميذ الطور الثانوي، وقد اعتمد الباحثان على المنهج الوصفي المسحي، تمثلت عينة الدراسة في أساتذة التربية البدنية والرياضية للطور الثانوي لولاية سوق أهراس المقدرة بعدد 40 أستاذا، بالاعتماد على استمارة استبيان، وتم استخدام اختبار كا لتحليل البيانات، وتوصل الباحثان إلى: - الفيديوهات الموجودة في هذه المنصة تسهل العملية التعليمية بتقديم محتوى تعليمي عالي الجودة من أي مكان وفي أي زمان ويتناسب مع احتياجات ومستوى التلاميذ،مما يعزز فهمهم واستيعابهم . - تعزيز التفاعل بين الأستاذ والتلاميذ من خلال الدردشة المتزامنة والغير متزامنة ومن خلال أدوات تقييم متقدمة بشكل مستمر ودقيق مما يساعد في تحديد نقاط القوة و الضعف. - تمكن الأساتذة من تصميم وتقديم محتوى تعليمي بطرق مبتكرة وجذابة تزيد من دافعية ورغبة التلاميذ في المشاركة و الممارسة وأوصى الباحثان: 1. ينبغي أن تكون الفيديوهات ذات جودة عالية من حيث الصورة والصوت، وأن تقدم شروحات واضحة ومفصلة للتقنيات الرياضية. 2. يجب أن تشمل المنصات موارد تعليمية إضافية مثل مقالات و دراسات وأبحاث تدعم المحتوى الرياضي. résumé : Notre étude vise à concevoir une plateforme numérique d'activités éducatives physiques et sportives pour les élèves du secondaire. Les chercheurs se sont appuyés sur la méthode d'enquête descriptive. L'échantillon de l'étude représentait les enseignants d'éducation physique et sportive du niveau secondaire de l'État du Souk. Ahras, estimé à 40 enseignants, sur la base d'un formulaire de questionnaire, et un test Ka a été utilisé pour analyser les données, et les chercheurs ont conclu : Les vidéos de cette plateforme facilitent le processus éducatif en fournissant un contenu éducatif de haute qualité, partout et à tout moment, adapté aux besoins et au niveau des étudiants, ce qui améliore leur compréhension et leur compréhension. - Améliorer l'interaction entre le professeur et les étudiants grâce à un chat synchrone et asynchrone et grâce à des outils d'évaluation avancés sur une base continue et précise, ce qui aide à identifier les forces et les faiblesses. - Permet aux enseignants de concevoir et de présenter du contenu éducatif de manière innovante et attrayante qui augmente la motivation des étudiants et leur désir de participer et de pratiquer. Les chercheurs ont recommandé : 1. Les vidéos doivent être de haute qualité en termes d’images et de son et fournir des explications claires et détaillées des techniques sportives. 2. Les plateformes doivent inclure des ressources éducatives supplémentaires telles que des articles, des études et des recherches qui soutiennent le contenu sportif.
Keywords: Digital platform; E-learning; Sports activities; منصة رقمية; التعليم الإلكتروني; الأنشطة الرياضية; Plateforme numérique; l'enseignement électronique; Activités sportives